Strategi Konvergensi Media TV Assunnah Cirebon dalam Optimalisasi Dakwah Digital - Arief Amarudin; Rokibullah Rokibullah; Dono Darsono; AS Haris Sumadiria (Jurnal Locus Penelitian dan Pengabdian, 2026)
The transformation of broadcasting media in the digital era requires local Islamic propagation institutions to adapt to media convergence so that dakwah messages remain relevant and reach audiences across generations. This study aims to analyze the media convergence strategy applied by TV Assunnah Cirebon in optimizing digital dakwah, covering the transition pattern from conventional broadcasting to digital platforms, content production and distribution strategies, as well as the challenges and opportunities accompanying the transformation process. The research uses a qualitative descriptive approach with a case study method, conducted through exploratory field research. Data were collected through in-depth interviews with TV Assunnah Cirebon managers, direct observation at the production studio and editing room, and documentation of digital content on various platforms, then analyzed using data triangulation techniques. The results show that TV Assunnah Cirebon applies a convergence strategy consisting of four main dimensions. First, the transition from satellite broadcasting to digital platforms as a strategic decision in response to the Analog Switch-Off (ASO) policy and high operational costs. Second, multiplatform integration through YouTube, Facebook, Instagram, TikTok, Telegram, and WhatsApp with content differentiation according to audience characteristics. Third, the implementation of the one content, multiple outputs production model accompanied by audio-visual quality standardization and distinctive Islamic visual branding. Fourth, strategic collaboration with dakwah networks such as Rodja TV, Ahsan TV, and ARTISI to expand reach. This study also identifies several challenges, including limited human resources, technical infrastructure, shadow banning, content reporting, and dynamics of digital regulation. These findings contribute to the literature on media convergence and dakwah communication, while also serving as a practical reference for other local dakwah institutions in designing adaptive and sustainable digital dakwah strategies.